FETUS PHANTOM CONSTRUCTIONS FOR OVERWEIGHT AND OBESE PREGNANT FEMALES FOR RADIOLOGICAL APPLICATIONS - Makkia, Rasha (East Carolina University, 2019)
Radiation exposure and associated radiation risks are major concerns for fetal development for pregnant patients in general, and in particular for overweight and obese pregnant patients who undergo diagnostic imaging or radiation therapy procedures. This dissertation describes a detailed research project related to the construction of hybrid computational phantoms, including the fetus and the pregnant female with the focus on overweight and obese patients, which can be used in radiological applications. In detail, a series of three hybrid computational fetus phantoms corresponding to a fetal age of 20, 31, and 35 weeks of pregnancy were constructed using highquality magnetic resonance imaging (MRI) sets obtained for three different patients. A total of 29 fetal organs were outlined from radiological images via the Velocity Treatment Planning System (TPS) and were imported to the three-dimensional (3D) modeling software package Rhinoceros for further reconstruction. The hybrid computational female phantom was constructed from the adult ICRP reference model which was converted from voxels into a non-uniform rational basis spline (NURBS) or mesh surface based phantom. A total of 35 different female organs and tissues were identified. All fetal and female organ masses were individually matched with the ICRP 89 Publication reference values. The hybrid computational pregnant female phantom series was constructed by individually adding the hybrid fetus model series to the hybrid female phantom. Fetal positions and locations were carefully adapted from MRI data and verified by a clinical specialist. Ultrasound data has also been used to determine the fetus body masses. Overweight and obese pregnant phantom models were derived from the developed standard hybrid computational pregnant series by adding different amounts of fat under the skin, except in the eye regions. They were carefully modeled using NURBS and/or polygon mesh geometry and include specified amounts of adipose tissue below the skin. The NURBS and mesh-based pregnant phantoms were then voxelized using the Binvox software and checked for consistency using the Viewvox and ImageJ software packages. This resulted in a set of pregnant female phantoms with body mass indexes ranging from 22.58 kg/m2 (normal body weight) to 34.24 kg/m2 (morbidly obese). This set of new phantoms can be used in the future to study the optimization of image quality and radiation dose for patients of different weight classifications. The ultimate goal is to create a library of all the data derived from these phantoms into a comprehensive dosimetry database defined in the Virtual Dose software. The new series of hybrid computational fetus models provide realistic anatomical details that can be useful in evaluating fetal radiation doses in pregnant patients undergoing diagnostic imaging or radiotherapy where realistic fetal computational human phantoms are required.
Keywords: Pregnant Phantoms; Fetus--Effect of radiation on; Obesity in women--Health and hygiene; Pregnancy--Nutritional aspects; Computer simulation; Pregnant women--Health and hygiene; Overweight Phantoms; Obese Phantoms; Computational Phantom Construction; Radiological Applications